Connective financing Chinese infrastructure projects and the diffusion of economic activity in developing countries - Bluhm, Richard; Dreher, Axel; Fuchs, Andreas; Parks, Bradley; Strange, Austin M.; Tierney, Michael J. (CESifo working papers, 2020)
This paper studies the causal effect of transport infrastructure on the spatial concentration of economic activity. Leveraging a new global dataset of geo-located Chinese government-financed projects over the period from 2000 to 2014 together with measures of spatial inequality based on remotely-sensed data, we analyse the effects of transport projects on the spatial distribution of economic activity within and between regions in a large number of developing countries. We find that Chinese-financed transportation projects reduce spatial concentration within but not between regions. In line with land use theory, we document a range of results which are consistent with a relocation of activity from city centers to their immediate periphery. Transport projects decentralize activity particularly strongly in regions that are more urbanized, located closer to the coast, and less developed.
Keywords: Graue Literatur